Blood Group Changed in a Patient with Acute Myelocytic Leukemia - Jahan, Shah Md. Sarwer; Kamruzzaman, A.K.M; Hossain, Md. Ismail; Matin, Md. Abdul; Hossain, Md. Zakir (Journal of Medicine, 2013)
Gain of red blood cell antigens has been described in patients with acute myelocytic leukemia (AML). This paper describes the gain of blood group A antigen in a patient with AML. At the time of diagnosis the patients red cells showed the 0 Rh (D) - phenotype. After induction of remission with one courses of Daunorubicin, Cytarabine, her blood group was changed to A Rh (D) - phenotype. DOI: http://dx.doi.org/10.3329/jom.v14i1.14559 J MEDICINE 2013; 14 : 77-79